Lactobacilli Interfere with Streptococcus pyogenes Hemolytic Activity and Adherence to Host Epithelial Cells - Saroj, Sunil D.; Maudsdotter, Lisa; Tavares, Raquel; Jonsson, Ann-Beth (Frontiers in Microbiology, 2016)
Streptococcus pyogenes [Group A streptococcus (GAS)], a frequent colonizer of the respiratory tract mucosal surface, causes a variety of human diseases, ranging from pharyngitis to the life-threatening streptococcal toxic shock-like syndrome. Lactobacilli have been demonstrated to colonize the respiratory tract. In this study, we investigated the interference of lactobacilli with the virulence phenotypes of GAS. The Lactobacillus strains L. rhamnosus Kx151A1 and L. reuteri PTA-5289, but not L. salivarius LMG9477, inhibited the hemolytic activity of S. pyogenes S165. The inhibition of hemolytic activity was attributed to a decrease in the production of streptolysin S (SLS). Conditioned medium (CM) from the growth of L. rhamnosus Kx151A1 and L. reuteri PTA-5289 was sufficient to down-regulate the expression of the sag operon, encoding SLS. The Lactobacillus strains L. rhamnosus Kx151A1, L. reuteri PTA-5289, and L. salivarius LMG9477 inhibited the initial adherence of GAS to host epithelial cells. Intriguingly, competition with a combination of Lactobacillus species reduced GAS adherence to host cells most efficiently. The data suggest that an effector molecule released from certain Lactobacillus strains attenuates the production of SLS at the transcriptional level and that combinations of Lactobacillus strains may protect the pharyngeal mucosa more efficiently from the initial colonization of GAS. The effector molecules released from Lactobacillus strains affecting the virulence phenotypes of pathogens hold potential in the development of a new generation of therapeutics.